Multinational companies and wage inequality in the host country: the case of Ireland - Paolo Figini; Holger Görg (Trinity College, Department of Economics, 1998)
In this paper, we analyse the effects of multinational companies on wage inequality in the host country, studying the case of the Irish economy. Based on a model developed by Aghion and Howitt (1998), in which the introduction of new technologies leads to increasing demand for skilled labour and, therefore, to rising inequality, we conduct an econometric study using data for the Irish manufacturing sector between 1979 and 1995. We examine inequality between wages for skilled and unskilled labour within the same manufacturing sector. Our results indicate that there is an inverted-U relationship between wage inequality and the presence of multinationals, i.e., with increasing presence of multinationals, wage inequality first increases, reaches a maximum and decreases eventually, ceteris paribus.
Keywords: D63; F23; J31; 330; Multinationales Unternehmen; Technologietransfer; Lohntheorie; Neue Wachstumstheorie; Theorie